What do asset prices have to say about risk appetite and uncertainty? - Geert Bekaert; Marie Hoerova; Martin Scheicher (European Central Bank (ECB), 2009)
Implied volatility indices should have information about risk parameters, once they are cleansed of the influence of normal volatility dynamics and macro-economic uncertainty. Building on intuition from the dynamic asset pricing literature, we uncover unobserved risk aversion and fundamental uncertainty from the observed time series of the VIX and the credit spreads while controlling for realized volatility, expectations about the macroeconomic outlook, and interest rates. We apply this methodology to monthly data from both Germany and the US. We find that implied volatilities contain a substantial amount of information regarding risk aversion whereas credit spreads have a lot to say about both risk aversion and uncertainty. Moreover, there is a significant comovement in the German and US risk aversion.
Keywords: 330; Credit Spread; Economic uncertainty; risk aversion; Time variation in risk and return; Volatility dynamics; Risikoaversion; Messung; Volatilität; CAPM; Konjunktur; Deutschland; USA